Combining different points of view on plant descriptions: mapping agricultural plant roles and biological taxa - Amardeilh, Florence; Aubin, Sophie; Bernard, Stephan; Bravo, Sonia; Bossy, Robert; Faron, Catherine; Michel, Franck; Raphel, Juliette; Roussey, Catherine (Frontiers in Artificial Intelligence, 2023)
This article describes our work on the alignment of two complementary knowledge graphs useful in agriculture: the thesaurus of cultivated plants in France named French Crop Usage (FCU) and the French national taxonomic repository TAXREF for fauna, flora and fungi. FCU describes the usages of plants in agriculture: 'tomatoes' are crops used for human food, 'grapevines' are crops used for human beverage. TAXREF describes biological taxa and associated scientific names: for example, a tomato species may be 'Solanum lycopersicum' or a grapevine species may be 'Vitis vinifera'. Both knowledge graphs contain vernacular names of plants but those names are ambiguous. Thus a group of agricultural experts produced some mappings from FCU crops to TAXREF taxa. Moreover, new RDF properties have been defined to declare those new types of mapping relations between plant descriptions. The metadata for the mappings and the mapping set are encoded with the Simple Standard for Sharing Ontological Mappings (SSSOM), a new model which, among other qualities, offers means to report on provenance, of particular interest for this work. The produced mappings are available for download in Recherche Data Gouv, the federated national platform for research data in France.